DLTS analysis of high resistive edge termination technique‐induced defects in GaN‐based Schottky barrier diodes. Issue 9 (31st March 2016) - Koné, Sodjan; Cayrel, Frederic; Yvon, Arnaud; Collard, Emmanuel; Alquier, Daniel
Abstract : Efficient edge terminations are fundamental for power electronic devices. High resistive edge termination technique obtained by ion implantation is a possible solution for GaN Schottky barrier diodes (SBD), but may induce defects detrimental to the devices. In this work, two sets of GaN SBDs, with or without a high resistive guard ring edge termination, were investigated by deep levels transient spectroscopy (DLTS). The corresponding DLTS spectra of devices with guard ring were compared to those of as‐fabricated devices (without). Four deep traps at 0.13, 0.26, 0.35, and 0.51 eV were observed below the conduction band in as‐fabricated structures while the ones with guard ring exhibit two additional levels at 0.47 and 0.80 eV and a strong enhancement in DLTS peaks magnitude. Further investigations showed that the additional traps detected in SBD devices with guard ring were consistent with ion implantation‐induced damages. These observations highlight the impact of high resistive edge termination technique on our devices and raise the need of optimization of such crucial structure for the improvement of GaN‐based Schottky barrier diode.